Changes in Blood Leukocyte Composition in Rats of Different Ages after Long-term Cold Adaptation - Lomako, Viktoria (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4): 268–273